Physical Fitness and Academic Performance in Normal Weight, Overweight, and Obese Schoolchild Handball Players in Qatar: A Pilot Study - Hermassi, Souhail; Hayes, Lawrence D.; Bragazzi, Nicola Luigi; Schwesig, René (Frontiers in Psychology, 2021)
This study aimed to investigate the relationships between physical fitness and academic performance in youth handball players of different BMI classifications. Thirty-three male handball players (age: 10.3 ± 0.61 years; body mass: 47.1 ± 12.1 kg; height: 1.43 ± 0.09 m; BMI: 23.1 ± 4.37 kg/m2; body fat: 20.6 ± 6.27%) were recruited from the Qatar handball first league and were assigned to their BMI age-adjusted groups (i.e., normal weight, overweight, and obese). Measurements included anthropometric data (height, mass, body mass index (BMI) and body fat percentage (%BF), and physical performance tests: agility T-half test; squat jump (SJ), and countermovement jump (CMJ), 10 and 15 m sprint; medicine ball throw (MBT). Aerobic capacity was evaluated using the Yo-Yo Intermittent Recovery Test level 1 (Yo-Yo IR1). Academic achievement was assessed through school records of grades point average (GPA) of Mathematics, Science and Arabic. None academic performance parameter and four physical performance parameters (agility T-half: p=0.035; CMJ: p=0.001; SJ: p=0.007; sprint 10 m: p=0.028) were different between BMI related groups. In 43% (3/7) of performance parameters and all academic parameters, the normal weight group showed the highest performance level, whereas the overweight group had the best performance in both sprint tests. The obese group was only superior in the medicine ball throw, but not at the p<0.05 level. A relevant relationship (r>0.5) between academic and physical performance parameters was only found between Yo-Yo IR 1 and science (r=0.548). A relevant correlation were found between CMJ and BMI (r=-0.569). The agility T-half test was correlated with CMJ (r=-0.614) and 10 m sprint (r=0.523). These findings suggest being overweight or obese are related to science academic performance among schoolchildren athletes in Qatar. Possibly, a normal BMI could positively influence academic performance. Physical education teachers, staff, and administrators should be cognizant that health promotion interventions improving composition may have the additional potential to improve dimensions of academic performance.